Go for zero tolerance: Cultural values, trust, and acceptance of zero-COVID policy in two Chinese societies - Huang, Yi-Hui Christine; Li, Jun; Liu, Ruoheng; Liu, Yinuo (Frontiers in Psychology, 2022)
This study seeks to explain the wide acceptance of the stringent zero-COVID policy in two Chinese societies—Mainland China (n = 2,184) and Taiwan (n = 1,128)—from perspectives of cultural values and trust. By employing the efficacy mechanism, this study identifies significant indirect effects of trust in government and key opinion leaders (KOL) on people’s policy acceptance in both societies. Namely, people who interpret the pandemic as a collectivist issue and who trust in government will be more accepting of the zero-COVID policy, whereas those who framed the pandemic as an individual issue tend to refuse the policy. Trust in government and KOLs foster these direct relationships, but trust in government functions as a more important mediator in both societies. The different contexts of the two Chinese societies make the difference when shaping these relationships. These findings provide practical considerations for governmental agencies and public institutions that promote the acceptance of the zero-COVID policy during the pandemic.